Pengaruh Sosial Media Marketing, Brand Position, Brand Equity pada Digital Marketing: Studi Empiris pada Sektor UMKM Makanan di Kecamatan Pakem - Pratiwi, Nurafida Ika; Pabulo, Azfa Mutiara Ahmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the influence of social media marketing, brand position, and brand equity on the effectiveness of digital marketing in the Micro, Small, and Medium Enterprises (MSMEs) food sector in Pakem District. In the ever-evolving digital era, MSMEs face challenges in utilizing technology in their marketing strategies. This study uses a quantitative method with data collection through questionnaires distributed to MSME actors in the area. The results of the analysis show that social media marketing has a significant positive effect on brand awareness and product sales, while a strong brand position and high brand equity also contribute to increasing customer loyalty and perceptions of product quality. These findings emphasize the importance of utilizing social media as a tool not only for promotion but also to build closer relationships with consumers. Thus, this study provides insight for MSME actors to optimize their digital marketing strategies in order to increase competitiveness and business growth, as well as being a reference for the government in formulating policies that support the development of MSMEs in the digital era.